Upregulation of mRNA Expression of ADGRD1/GPR133 and ADGRG7/GPR128 in SARS-CoV-2-Infected Lung Adenocarcinoma Calu-3 Cells - Žáčková, Sandra; Pávová, Marcela; Trylčová, Jana; Chalupová, Jitka; Priss, Anastasiia; Lukšan, Ondřej; Weber, Jan (Cells, 2024)
Adhesion G protein-coupled receptors (aGPCRs) play an important role in neurodevelopment, immune defence and cancer; however, their role throughout viral infections is mostly unexplored. We have been searching for specific aGPCRs involved in SARS-CoV-2 infection of mammalian cells. In the present study, we infected human epithelial cell lines derived from lung adenocarcinoma (Calu-3) and colorectal carcinoma (Caco-2) with SARS-CoV-2 in order to analyse changes in the level of mRNA encoding individual aGPCRs at 6 and 12 h post infection. Based on significantly altered mRNA levels, we identified four aGPCR candidates-ADGRB3/BAI3, ADGRD1/GPR133, ADGRG7/GPR128 and ADGRV1/GPR98. Of these receptors, ADGRD1/GPR133 and ADGRG7/GPR128 showed the largest increase in mRNA levels in SARS-CoV-2-infected Calu-3 cells, whereas no increase was observed with heat-inactivated SARS-CoV-2 and virus-cleared conditioned media. Next, using specific siRNA, we downregulated the aGPCR candidates and analysed SARS-CoV-2 entry, replication and infectivity in both cell lines. We observed a significant decrease in the amount of SARS-CoV-2 newly released into the culture media by cells with downregulated ADGRD1/GPR133 and ADGRG7/GPR128. In addition, using a plaque assay, we observed a reduction in SARS-CoV-2 infectivity in Calu-3 cells. In summary, our data suggest that selected aGPCRs might play a role during SARS-CoV-2 infection of mammalian cells.
Keywords: COVID-19; ADGRD1; lidé; Caco-2 Cells; upregulace; ADGRG7; Cell Line, Tumor; GPR128; Caco-2 buňky; nádory plic; messenger RNA; RNA, Messenger; Adenocarcinoma of Lung; Humans; mRNA expression; adhesion GPCR; Receptors, G-Protein-Coupled; Caco-2; receptory spřažené s G-proteiny; adenokarcinom plic; SARS-CoV-2; GPR133; nádorové buněčné linie; Up-Regulation; Calu-3; Lung Neoplasms